2013
DOI: 10.1007/s11284-013-1110-5
|View full text |Cite
|
Sign up to set email alerts
|

Variation in soil respiration under the tree canopy in a temperate mixed forest, central China, under different soil water conditions

Abstract: The forest canopy cover can directly and indirectly affect soil conditions and hence soil carbon emission through soil respiration. Little is known, however, on the effects of canopy cover on soil respiration under the canopy of different tree species and soil water conditions. We have examined the variation in soil respiration at different soil water conditions (dry <10 %, wet >20 %, v/v) under different tree canopy covers in comparison with the canopy interspace in a temperate coniferous (Pinus armandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 50 publications
7
31
0
1
Order By: Relevance
“…Generally, CO 2 efflux correlates positively with soil temperature and negatively with soil moisture (Davidson et al, 1998;Kosugi et al, 2007;Liu et al, 2013), as verified by our study (Fig. 4).…”
Section: Drivers Of Soil Co 2 Effluxsupporting
confidence: 86%
See 2 more Smart Citations
“…Generally, CO 2 efflux correlates positively with soil temperature and negatively with soil moisture (Davidson et al, 1998;Kosugi et al, 2007;Liu et al, 2013), as verified by our study (Fig. 4).…”
Section: Drivers Of Soil Co 2 Effluxsupporting
confidence: 86%
“…Increased canopy cover maintains soil moisture (Lin et al, 2006;Liu et al, 2013), as observed in our study (Fig. 2), due to a decrease in soil evaporation (Lin, 2010).…”
Section: Systemsupporting
confidence: 78%
See 1 more Smart Citation
“…For example, canopy shading and rainfall interception (especially for small rainfall events) could have caused the observed variation in soil moisture between the guava‐invaded sites and uninvaded sites. The above explanation is supported by observations by Shi et al () and Liu et al, () that canopy structure and size influence soil moisture and temperature. The high soil moisture content observed in guava‐invaded sites has a bearing on soil compaction, with invaded soils being less compact than uninvaded soils, although this was observed only in April and May.…”
Section: Discussionsupporting
confidence: 76%
“…The observed high soil moisture content in April and May underneath guava‐invaded sites as compared to uninvaded sites could be a result of several factors, for example the spatial distribution of individual trees (Luan, Liu, Zhu, Wang, & Liu, ), canopy cover (McCarthy & Brown, ), litter production (Reichstein et al, ) and variations in soil respiration (Liu et al, ). For example, canopy shading and rainfall interception (especially for small rainfall events) could have caused the observed variation in soil moisture between the guava‐invaded sites and uninvaded sites.…”
Section: Discussionmentioning
confidence: 99%